2020
DOI: 10.29333/iji.2020.13132a
|View full text |Cite
|
Sign up to set email alerts
|

Project Based Learning and Academic Procrastination of Students in Learning Physics

Abstract: Learning physics at SMA, does not only involve memorizing facts, but it also engages the students in solving more problems without delay and attaining a real learning achievement. This study aimed to analyze the effect of project-based learning (PjBL) compared with direct instruction (DI) and student procrastination on student cognitive achievement in learning physics. This quasi-experimental study used a pretest-posttest non-equivalent control group design, involving 9 classes or 278 students of class X MIPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 17 publications
(30 reference statements)
4
41
0
7
Order By: Relevance
“…Students who have LAP show critical thinking skills is significantly higher than students who have HAP. The results of this study are in accordance with previous studies [28]. Quantitatively, the average value of critical thinking skills that can be achieved by students who have LAP is M = 45.62 with SD = 12.72, in the low category, while those achieved by students who have HAP are M = 36.94; SD = 12.29 with very low category.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Students who have LAP show critical thinking skills is significantly higher than students who have HAP. The results of this study are in accordance with previous studies [28]. Quantitatively, the average value of critical thinking skills that can be achieved by students who have LAP is M = 45.62 with SD = 12.72, in the low category, while those achieved by students who have HAP are M = 36.94; SD = 12.29 with very low category.…”
Section: Discussionsupporting
confidence: 91%
“…The low academic procrastination will make students achieve higher learning achievement [27]. In learning physics class X senior high school, it is stated that students who have low academic procrastination show higher learning outcomes than those who have high academic procrastination [28].…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with research conducted by (Jamilla et al, 2020), which revealed that the project-based learning model assisted by Google's classroom using instructional videos has a positive impact in the learning process, where the model must be designed in such a way according to student characteristics and material learning that will be applied during the learning process in order to improve students' ability to receive lessons and improve learning outcomes to be more effective when the learning process takes place. Likewise according to (Santyasa et al, 2020) revealed in his research that there are significant differences in academic achievement between students studying in the PjBL and DI models. Which higher academic achievement is achieved by students studying with the PjBL model.…”
Section: The Effect Of Project Based E-learning Models (Pjbel) On Student Learning Outcomesmentioning
confidence: 99%
“…In addition, students feel that the existence of project-based learning assisted by e-learning can improve their skills in working together in groups, innovating in creating something new, utilizing existing learning resources and useful technology in the world of education. (Santyasa et al, 2020) also revealed in his research that there were significant differences in academic achievement between students studying in the PjBL and DI models. Which higher academic achievement is achieved by students studying with the PjBL model.…”
mentioning
confidence: 94%
“…Furthermore, research on the combination of PjBL with the flipped classroom approach has been carried out with results in science subjects showed that the combination of the flipped classroom and the PjBL model has a positive effect on students' critical thinking skills [5]. In addition, a project-based learning approach with flipped classrooms helped in improving students' achievement in learning mathematics in various cognitive styles [11]. Chemistry subjects are in the same subject family as mathematics and science, so that this learning model is expected to give the same effect on chemistry learning achievement.…”
Section: Introductionmentioning
confidence: 99%